Optimizing Productive Waqf Funds for the Development of Religious Tourism at the Central Java Grand Mosque - Angel Livansyah; Fania Mutiara Savitri; Dedy Susanto; Lukmanul Hakim (Jurnal Dakwah Risalah, 2025)
Productive Waqf, Religious Tourism, Central Java Grand Mosque, Islamics Economy, SWOT Analysis The development of religious tourism based on productive waqf funds can serve as an alternative solution to support the financial sustainability of religious tourism destinations in Indonesia. This study focuses on examining the productive waqf fund management system implemented at the Central Java Grand Mosque (MAJT), as well as formulating optimization strategies for productive waqf funds to enhance the potential of the religious tourism sector at MAJT. This research employs a qualitative approach using a case study method at the Banda Masjid Agung Semarang Waqf Nadzir Foundation. Data were collected through interviews, field observations, and document analysis. The findings indicate that MAJT has implemented an institutional-based productive waqf fund management system that is integrated, professional, and transparent. However, despite the transparent and professional management practices, several challenges remain, including limited funding capacity, role duality within the organizational structure, and suboptimal utilization of technology. To optimize waqf fund management, the recommended strategies include the development of a more standardized management model, the empowerment of micro, small, and medium enterprises (MSMEs), diversification of religious tourism products, and the optimization of cash waqf and waqf-linked sukuk. This study is expected to contribute an integrative framework for enhancing the effectiveness of productive waqf management models in the Islamic tourism sector through strategic implementation aimed at promoting equitable and sustainable religious tourism development.